Wymarzony prezent pod choinkę. O zabawkach świątecznych w literaturze i czasopismach adresowanych do dzieci II połowy XIX i początku XX wieku - Kabacińska-Łuczak, Katarzyna; Nawrot-Borowska, Monika (Studia Edukacyjne, 2018)
Timeless attributes of children’s games, i.e. toys, have been made the subject of research. The authors focus on the toys received by children from Polish families during Christmas. The aim of these analyses is therefore to characterise Christmas children’s toys presented in two types of sources intentionally addressed to children: children’s literature and press. The research covers the second half of the 19th century and the beginning of the following century. The article in its subject matter refers to the Authors’ earlier research on Christmas toys and is in line with the ever developing trend of research on toys from the historical and pedagogical perspective.